Republic of Kazakhstan : 2019 Article IV Consultation-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2020)
The political transition has increased the focus on social conditions and regional and rural development. Growth has been buoyed by new spending, retail credit, and oil and gas investments. Inflation has picked up, and the current account has deteriorated. Renewed fiscal consolidation is planned from 2020. Non-oil growth is expected to moderate to 4 percent (potential), as construction, fiscal stimulus, and household borrowing ease. Growth could be higher if decisive reforms drive productivity gains. The state continues to play a strong role in the economy, and the authorities face challenges ensuring that measures are well targeted and effective in promoting private sector growth. The challenges include oil volatility and dependency, reliance on subsidies and other state support, still-impaired banks, and governance vulnerabilities. The authorities are exploring ways to strengthen the fiscal framework, assessing monetary and exchange policies, undertaking a bank asset quality review (AQR), and establishing an independent financial sector regulator. Progress is being made on headline reforms, but ensuring decisive changes on the ground remains a challenge. Risks relate to oil prices and trading partner growth.